Association of Serum IgE with Keratoconus - Raihan, Mohammad Hussain; Khan, Md Kamrul Hasan; Kajmina, Natasha; Rahman, Md Mahbubur; Rashid, Md Shoeb Ur; Shuchi, Tarzeen khadiza (Journal of National Institute of Ophthalmology, 2022)
Purpose: Keratoconus is an ectatic corneal disease characterized by regional thinning and protrusion that leads to irregular astigmatism and, ultimately, substantial vision impairment. The aim of this study was to see if there was a link between serum IgE levels and keratoconus. Methods: At the Combined Military Hospital Dhaka, a prospective observational study was conducted in the general Eye OPD and Cornea clinic. The study involved 60 participants who were divided into 2 groups. Thirty people with keratoconus were assigned to Group A, while 30 healthy people were assigned to Group B. All 60 patients had their serum IgE levels checked. Results: The mean age of the study subjects in Group A and group B were 19.60±5.28 (SD), and 20.23±5.62 (SD) respectively; 13 were male and 17 were female in Group-A, and 10 were male and 20 were female in Group-B. Serum IgE was 243.183±143.059 (SD) in group-A and 86.067±77.065 (SD) in group-B. There was a significant rise in serum IgE in Group-A (p value <0.0001). Conclusion: Elevated serum IgE levels are strongly associated with keratoconus. Measuring serum IgE could be an important parameter in the management of Keratoconus. J. Natl. Inst. Ophthalmol. 2022; 5(2):21-24